Strategi Resiliensi SDM PMII di Era Digital 5.0: Pendekatan 7S McKinsey Framework - M. Adi Trisna Wahyudi; M. Zulfa ‘Ulumuddin Alwy; Kusnul Ciptanila Yuni K; M. Syam’un Rosyadi; Ismi Rojayanti (Journal of Islamic Management, 2025)
This study aims to explore the application of Human Resources (HR) resilience strategies in the context of youth organizations, especially the Indonesian Islamic Student Movement (PMII), in the Digital 5.0 era. Using the McKinsey 7S Framework approach, this study focuses on how the seven main elements of the organization strategy, structure, system, staff, skills, management style, and shared values affect organizational and HR resilience in facing challenges and opportunities caused by advances in digital technology. This study adopts a qualitative approach with in-depth interviews and SWOT analysis to identify driving and inhibiting factors in building resilient HR. The results of the study indicate that digital literacy, adaptation skills, and strengthening social networks are important components in developing HR resilience. This study provides an important contribution to the development of strategic policies and programs in youth organizations in Indonesia